2021
DOI: 10.3390/atmos12070865
|View full text |Cite
|
Sign up to set email alerts
|

Simulations of the East Asian Winter Monsoon on Subseasonal to Seasonal Time Scales Using the Model for Prediction Across Scales

Abstract: The Model for Prediction Across Scales (MPAS) is used to simulate the East Asian winter monsoon (EAWM) over the 2011–2020 winter. The 45 day hindcasts are made with 30 km horizontal resolution and constructed to a time-lagged ensemble system. The climatology, the major modes of EAWM variability, and the blocking activities are examined. The evaluation results reveal that MPAS can simulate the climatologic characteristics of EAWM reasonably, with a surface cold bias of 4% and a positive rainfall bias of 9% over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 92 publications
1
2
0
Order By: Relevance
“…However, the specific causes of the low prediction skill with regard to changes in equatorial surface temperature variability or Arctic-related circulation, need to be further investigated using a more comprehensive analysis. Consistently with this study, Hsu et al [39] recently revealed that tropical sea surface temperature biases are related to the EAWM variability in the subseasonal simulation for 2011-2020. In this study, although the hindcast period is limited to 1991-2010 due to data availability, it will be extended to more recent periods (e.g., 2011-2020) after updating the model version.…”
Section: Discussionsupporting
confidence: 90%
“…However, the specific causes of the low prediction skill with regard to changes in equatorial surface temperature variability or Arctic-related circulation, need to be further investigated using a more comprehensive analysis. Consistently with this study, Hsu et al [39] recently revealed that tropical sea surface temperature biases are related to the EAWM variability in the subseasonal simulation for 2011-2020. In this study, although the hindcast period is limited to 1991-2010 due to data availability, it will be extended to more recent periods (e.g., 2011-2020) after updating the model version.…”
Section: Discussionsupporting
confidence: 90%
“…The Model for Prediction Across Scales-Atmosphere (MPAS-A) is a global, non-hydrostatic atmospheric model with the unstructured Voronoi meshes and C-grid, which developed with the basis of WRF model (Skamarock et al 2012). MPAS model has been used for seasonal and sub-seasonal forecasts (Weber and Mass 2019;Hsu et al 2021). Chen et al (2023 conducetd two set of climate simulations from April to August over China, and evaluated the surface air temperature and precipitation during the East Asia summer mosoon using CN05 observation.…”
Section: Introductionmentioning
confidence: 99%
“…Spherical icosahedral grid is often used as the basic framework of atmospheric models, such as the ICosahedral Nonhydrostatic model (ICON) [1-3], Models for Predication Across Scales (MPAS) [4], the Non-hydrostatic ICosahedral Atmospheric Model (NICAM) [5], DYNAMICO [6], Ocean-Land-Atmosphere Model (OLAM) [7,8], etc. These models are wieldy used for polar lows simulation [9], monsoon simulation [10], ocean tides dissipation [11], etc. Recently, the Spectral Radiation Transport Model for Aerosol Species coupled with NICAM (NICAM-SPRINTARS) [12] has been developed for studying and simulating atmosphere-aerosols interactions and their effects on atmospheric pollution and climate change.…”
Section: Introductionmentioning
confidence: 99%